EMPOWERING INDIGENOUS STUDENTS THROUGH DIGITAL SKILLS AND CROSS-CULTURAL LITERACY: A COMMUNITY SERVICE PROGRAM IN MALAYSIA - Gusman Nawanir; Abrar Abrar; Dian Saputra; Rahmat Setiawan; Febrian Lisman (Komunitas Manajemen Kompetitif, 2026)
This community service program aimed to empower Orang Asli (indigenous) students in Pahang, Malaysia, by enhancing their digital literacy and cross-cultural competencies. The program addressed the digital divide faced by indigenous students in higher education. A one-day intensive bootcamp was conducted on February 13, 2026, involving 30 participants from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and University College of Yayasan Pahang (UCYP). The methods included hands-on training on basic productivity software (Google Workspace, Microsoft Office), digital safety education, and career platform introduction. Partner satisfaction surveys showed 100%